Low-temperature fired white Yellow River sediment glass ceramic and preparation method thereof

Through the cooperation of low-temperature firing method and specific flux and nucleating agents, the shortcomings of Yellow River sediment in microcrystalline glass production were successfully solved, and low-cost and high-performance white microcrystalline glass preparation was achieved.

CN119612963APending Publication Date: 2025-03-14YELLOW RIVER INST OF HYDRAULIC RES YELLOW RIVER CONSERVANCY COMMISSION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411740546.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, there are few researches on the preparation of microcrystalline glass using Yellow River sediment, which leads to insufficient sources of raw materials for microcrystalline glass and high production costs.

Method used

The low-temperature firing method is adopted to prepare white microcrystal glass by mixing the Yellow River sediment with other raw materials in a specific ratio, and through steps such as melting, forming, nucleation and crystallization. In this method, B2O3-CuO oxide is added as flux, K2CO3 and CaCO3 are used as flux, and Na2SiF6, TiO2 and chromite are selected as nucleating agents to reduce the melting temperature and crystallization activation energy.

Benefits of technology

It has achieved the preparation of white microcrystalline glass with Yellow River silt as raw materials at lower temperatures, reducing production costs and improving product performance indicators, such as bending strength and impact toughness, which meets the requirements of green building materials and industrial microcrystalline glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612963A_ABST
    Figure CN119612963A_ABST
Patent Text Reader

Abstract

The invention relates to low-temperature fired white Yellow River sediment microcrystalline glass and a preparation method thereof. The low-temperature fired white Yellow River sediment microcrystalline glass comprises the following raw materials: 50-65% of Yellow River sediment, 15-25% of CaCO3, 5-10% of dolomite, 3-10% of silica sand, 1-5% of Na2SiF6, 1-5% of K2CO3, 1-5% of chromite and 1-5% of TiO2. B2O3-CuO accounting for 1%-4% of the total weight of the raw materials is added. The preparation method comprises the following steps: (1) melting raw materials to obtain basic molten glass; (2) molding the molten glass to obtain a glass plate; and (3) coring and crystallizing the glass plate, and then carrying out post-treatment. The microcrystalline glass is prepared by firing the Yellow River silt at low temperature, a new way is provided for high-value utilization of Yellow River silt resources, and the product is high in quality and low in cost and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for low-temperature firing of white microcrystalline glass using Yellow River silt as a main raw material, belonging to the high-tech field of microcrystalline glass. Background Art

[0002] As a silicate resource, how to make high-value comprehensive utilization of the Yellow River sediment and turn waste into treasure has always been an important research direction. In recent years, the Yellow River sediment has been widely used in building materials (sintered bricks, autoclaved bricks, ceramsite, etc.), industrial materials (molding sand, coated sand, etc.), flood control materials (artificial stone, slope protection bricks, etc.), agricultural materials (saline-alkali land improvement, greening planting soil, etc.), and artworks (mud inkstones, pottery, etc.).

[0003] At present, glass-ceramics mainly use industrial waste slag, industrial tailings, solid waste ash, etc. as raw materials. For example, the patent with application number CN201610294821.X discloses a cyanide tailings foamed glass-ceramics and its preparation method. Its main raw material is cyanide tailings (industrial waste slag), and foaming agent, nucleating agent, solvent and foam stabilizer are added to make glass-ceramics through preheating, foaming, crystallization and annealing. This invention uses cyanide tailings produced in gold smelting as the main raw material to prepare foamed glass-ceramics. However, there are few related studies on the use of Yellow River sediment to prepare glass-ceramics. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing white glass-ceramics by low-temperature sintering of Yellow River sediment.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A low-temperature fired white Yellow River sediment glass-ceramics, the raw material composition by weight percentage is: Yellow River sediment 50%-65%, CaCO3 15%-25%, dolomite 5%-10%, silica sand 3%-10%, Na2SiF6 1%-5%, K2CO3 1%-5%, chromite 1%-5%, TiO2 1%-5%; in addition, B2O3-CuO oxide is added in an amount of 1%-4% of the total weight of the raw materials.

[0007] The pH value of the Yellow River sediment is 7.5-9, and the median particle size D 50 The median particle size of the dolomite is D50 The median particle size of the silica sand is 320 nm, and the main components are: CaO 63% to 70%, MgO 27% to 35%, SiO2 1% to 5%, Al2O3 0.01% to 2%, Fe2O3 0.01% to 1%, CuO 0.01% to 1%, and Cr2O3 0.01% to 1%. 50 The chromite has a median particle size of 470 nm and its main components are: SiO2 97% to 99%, Al2O3 0.01% to 3%, K2O 0.01% to 1%, CaO 0.01% to 1%, Fe2O3 0.01% to 1%, Cr2O3 0.01% to 1%, TiO2 0.01% to 1%, and CuO 0.01% to 1%. 50 The diameter of the CaCO3 is 420nm, and the main components are: Cr2O3 42% to 51%, Fe2O3 25% to 33%, Al2O3 8% to 16%, MgO 5% to 10%, SiO2 1% to 5%, and TiO2 0.01% to 1%. The purity of the CaCO3 is greater than 95%, and the median particle size D 50 450nm; Na2SiF6 purity is greater than 95%, D 50 350nm; K2CO3 purity is greater than 95%, D 50 410nm; TiO2 purity is greater than 95%, D 50 The molar ratio of B2O3 to CuO in the B2O3-CuO oxide is 1:1, wherein the purity of B2O3 is greater than 99%, and D 50 390nm; CuO purity is greater than 99%, D 50 It is 440nm.

[0008] The low-temperature firing method of the white Yellow River sediment glass-ceramics comprises the following steps:

[0009] (1) Melting: Place the Yellow River silt in an oven for drying, then mix it evenly with other raw materials according to the proportion, pour it into a lifting muffle furnace, slowly heat it to 1330℃~1350℃ for sintering, and keep it at this temperature for 2h~3h to ensure that all the materials are melted to obtain glass liquid; (2) Molding: Pour the molten glass liquid into a mold at 400℃~600℃, cool it for 20s~30s, and obtain a glass plate; (3) Nucleation: Place the glass plate in a muffle furnace and heat it at 2℃ / mi (4) Crystallization: raising the temperature of the muffle furnace from 600°C to 720°C-760°C at a heating rate of 2°C / min-5°C / min to nucleate the glass plate for 2h-4h; (5) Post-processing: cutting and polishing the semi-finished microcrystalline glass to obtain a finished product.

[0010] Beneficial effects of the present invention

[0011] (1) The present invention uses Yellow River silt as raw material. The Yellow River silt resources are abundant and cheap and easy to obtain. It not only solves the problem of the source of raw materials for microcrystalline glass, but also provides a new way for the high-value utilization of Yellow River silt resources. At the same time, it can greatly reduce the production cost of microcrystalline glass, and has good economic and social value.

[0012] The main chemical components of the microcrystalline glass of the present invention are SiO2, Al2O3, CaO, and auxiliary materials such as a crystal nucleating agent. The basic glass is a CaO-Al2O3-SiO2 system, and the microcrystalline glass with natural marble patterns and texture is obtained.

[0013] (2) The present invention reduces the melting temperature of microcrystalline glass from the usual 1500°C to below 1350°C by controlling the particle size of the raw materials and the amount of flux added and used, thereby significantly reducing the preparation cost of microcrystalline glass.

[0014] (3) The present invention utilizes the properties of the Yellow River silt as a silicate material. The raw material itself contains a certain amount of SiO2, Al2O3, CaO, Fe2O3, etc. By pre-treating the silt raw material, the ferromagnetic substances in the Yellow River silt are mainly removed, which is conducive to the formation of microcrystalline glass with xonotlite as the main crystal phase.

[0015] (4) The present invention takes into account that the relative content of SiO2 in the Yellow River sediment is relatively high and the melting temperature of the basic raw materials is relatively high. K2CO3 and CaCO3 are selected as fluxes to reduce the melting point of the vitrification of the Yellow River sediment. At the same time, binary oxide B2O3-CuO is selected as flux. 3+ , Cu 2+Entering the interstitial sites between the [Si(Al)O4] tetrahedrons will form an interstitial solid solution, causing lattice distortion and promoting grain boundary migration, reducing the sintering activation energy, thereby achieving sintering at a lower temperature, which can effectively reduce energy consumption in the production process.

[0016] (5) The present invention uses three nucleating agents, Na2SiF6, TiO2 and chromite, to effectively reduce the crystallization activation energy of the Yellow River sediment glass-ceramics, so that the surface of the glass-ceramics is crystallized as a whole, and the glass-ceramics has excellent physical and chemical properties. 4+ Replace Si in the silicon-oxygen tetrahedron in a four-coordinate manner 4+ , thereby achieving better miscibility; at the same time F - Radius and O 2- Radius close, F - Can replace O in silicon-oxygen tetrahedron 2- ; During the melting process of chromite, high field strength ions Cr 6+ The existence of 6+ The surrounding oxygen ions are more ordered, which can cause the destruction of the silicate network structure. The simultaneous use of three nucleating agents can make the silicon-oxygen network structure easier to break, thereby weakening the glass network structure and inducing two-phase separation and crystal nucleation in the glass.

[0017] (6) In the process of preparing microcrystalline glass with xonotlite as the main crystal phase, the problem of insufficient SiO2 content in the basic glass composition is effectively solved by adding silica sand with a high SiO2 content.

[0018] (7) The present invention uses Yellow River silt as raw material to prepare white glass-ceramics at a relatively low firing temperature, which can greatly reduce the production cost of glass-ceramics. The product has good performance, with a bending strength greater than 102 MPa and an impact toughness greater than 3.7 kJ / m 2 , green and environmentally friendly, in line with the requirements of green building materials and JC / T 2097-2011 "Industrial Microcrystalline Glass Sheets", can be used in architectural decoration, machinery manufacturing, microelectronics technology, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Yellow River sediment XRD pattern;

[0020] Figure 2 The white Yellow River sediment glass-ceramics of Example 1;

[0021] Figure 3 SEM image of the white Yellow River sediment glass-ceramics of Example 1;

[0022] Figure 4 XRD pattern of white Yellow River sediment glass-ceramics of Example 1;

[0023] Figure 5 FTIR image of white Yellow River sediment glass-ceramics of Example 1. DETAILED DESCRIPTION

[0024] The specific implementation methods of the present invention are further described in detail below in conjunction with the examples. Unless otherwise specified, the instruments and equipment involved in the examples are all conventional instruments and equipment; the raw materials involved are all commercially available conventional raw materials; and the test methods involved are all conventional methods.

[0025] Example 1 A low temperature fired white Yellow River sediment glass-ceramic

[0026] The raw material composition by weight percentage is: Yellow River silt 58.0%, CaCO3 18.9%, dolomite 7.8%, silica sand 5.8%, Na2SiF6 3.1%, K2CO3 2.9%, chromite 2.3%, TiO2 1.2%, plus 1.5% B2O3-CuO oxide of the total weight of the above raw materials.

[0027] The Yellow River silt is obtained after washing, scrubbing, and magnetic separation. The main components of the treated Yellow River silt are: SiO281.47%, Al2O310.50%, CaO 1.15%, Fe2O30.56%, K2O 3.51%, MgO 0.34%, Na2O2.12%, TiO20.10%, the pH value of the silt is 8.85, and the median particle size D 50 450nm;

[0028] The water washing is performed by using a hydraulic classifier for 2 to 3 times, and the scrubbing is performed by using a spiral scrubbing machine for 2 to 3 times; the magnetic separation uses a 25000GS fully automatic magnetic separator to remove ferromagnetic substances in the sediment.

[0029] The main components of dolomite are: CaO 67.29%, MgO 30.45%, SiO21.25%, Al2O30.66%, Fe2O30.21%, CuO 0.04%, Cr2O30.04%, median particle size D 50 320nm; the main components of silica sand: SiO297.85%, Al2O31.50%, K2O 0.25%, CaO 0.17%, Fe2O30.12%, Cr2O30.04%, TiO20.04%, CuO 0.03%, median particle size D 50 470nm; the main components of chromite: Cr2O345.79%, Fe2O329.59%, Al2O311.72%, MgO 7.72%, SiO23.54%, TiO20.63%, median particle size D 50is 420nm; the purity of CaCO3, Na2SiF6, K2CO3 and TiO2 is greater than 95%.

[0030] Preparation method of B2O3-CuO oxide: B2O3 and CuO were ball milled twice by high-energy ball mill at a speed of 2500r / min for 3min and 5min respectively. The obtained oxide D 50 Less than 500nm, the median particle size of B2O3 is D 50 The median particle size of CuO is 390nm. 50 The particle size is 440nm, the purity of B2O3 and CuO are both greater than 99%, and the molar ratio of B2O3 and CuO is 1:1.

[0031] The preparation method comprises the following steps:

[0032] (1) Melting: Place the Yellow River silt in an oven to dry, then mix it evenly with other raw materials in a certain proportion, pour it into a lifting muffle furnace, slowly heat it to 1350°C, and then keep it warm for 2 hours to ensure that all the materials are melted;

[0033] (2) Molding: Pour the molten glass into a mold at 600°C and cool for 20 seconds to obtain a glass plate. Immediately place the glass plate into a muffle furnace at 600°C to prepare for nucleation and crystallization.

[0034] (3) Nucleation: The glass plate is nucleated by heating the muffle furnace from 600°C to 740°C at a heating rate of 5°C / min for 2 h.

[0035] (4) Crystallization: The glass plate is crystallized by heating the muffle furnace to 880°C at a heating rate of 5°C / min for 3 hours, and then cooled to room temperature in the furnace to obtain a white microcrystalline glass semi-finished product;

[0036] (5) Post-processing: cutting and polishing the semi-finished glass-ceramic products to obtain finished products.

[0037] The performance indicators of the obtained microcrystalline glass are shown in Table 1.

[0038] Table 1 Performance indexes of white microcrystalline glass in Example 1

[0039] Performance Indicators result Bulk density <![CDATA[2.74g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.071g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.6% Alkali resistance (20% NaOH) 99.3% Impact toughness <![CDATA[4.26kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 118.06MPa Vickers hardness <![CDATA[703kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.2]]>

[0040] Figure 1 The XRD diagram of the raw material Yellow River sediment is shown in Figure 2. It can be seen that the main components of the treated Yellow River sediment are quartz, feldspar and other substances.

[0041] Figure 2 This is the product photo of the white Yellow River sediment glass-ceramics of Example 1.

[0042] Figure 3 This is a SEM image of the white microcrystalline glass after HF etching in Example 1. It can be seen that the glass phase is completely dissolved, presenting a columnar structure with xonotlite as the main crystal phase, the crystals are complete and sufficient, the structure is dense, and the glass phase and the crystal phase are interlocked.

[0043] Figure 4 This is the XRD pattern of the glass-ceramics of the white Yellow River sediment in Example 1. Analysis of the basic components of the glass-ceramics shows that the system belongs to the ternary system of SiO2, Al2O3, and CaO, the crystal phase is xonotlite, and the grain size calculated by the Scherrer formula is 48.33 nm.

[0044] Figure 5 This is the FTIR image of the white Yellow River sediment glass-ceramics of Example 1. It can be seen that there are three infrared absorption bands in the FTIR spectrum, located at 900 cm -1 ~1200cm -1 、750cm -1 ~850cm -1 and 400cm -1 ~500cm -1 . Among them, 400cm -1 ~500cm -1 The absorption band at 750 cm-1 is attributed to Si-O-Si bending vibration. -1 ~850cm -1 The absorption band at 900cm is caused by the stretching vibration of Si-O-Al and the symmetric stretching vibration of Si-O-Si. -1 ~1200cm -1 The absorption bands correspond to the antisymmetric stretching vibration of Si-O-Si and the vibration of Si-O.

[0045] Example 2 A low temperature fired white Yellow River sediment glass-ceramic

[0046] The raw material composition by weight percentage is: Yellow River silt 58.6%, CaCO3 19.0%, dolomite 7.9%, silica sand 5.8%, Na2SiF6 2.3%, K2CO3 2.9%, chromite 2.3%, TiO2 1.2%, plus 1.5% B2O3-CuO oxide of the total weight of the above raw materials.

[0047] The performance requirements and preparation methods of the raw materials are the same as those in Example 1. The performance indicators of the obtained microcrystalline glass are shown in Table 2.

[0048] Table 2 Performance indexes of white microcrystalline glass in Example 2

[0049] Performance Indicators result Bulk density <![CDATA[2.73g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.073g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.4% Alkali resistance (20% NaOH) 99.1% Impact toughness <![CDATA[4.01kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 115.56MPa Vickers hardness <![CDATA[695kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.2]]>

[0050] Example 3 A low temperature fired white Yellow River sediment glass-ceramic

[0051] The raw material composition by weight percentage is: Yellow River silt 62.0%, CaCO3 15.3%, dolomite 7.9%, silica sand 6.1%, Na2SiF62.3%, K2CO3 2.9%, chromite 2.3%, TiO2 1.2%, plus 1.5% B2O3-CuO oxide of the total weight of the above raw materials.

[0052] The properties of the raw materials and the preparation method are the same as those in Example 1. The performance indicators of the obtained microcrystalline glass are shown in Table 3.

[0053] Table 3 Performance indexes of white microcrystalline glass in Example 3

[0054] Performance Indicators result Bulk density <![CDATA[2.71g / cm 3 ]]> Water absorption 0.02% Wear <![CDATA[0.074g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.2% Alkali resistance (20% NaOH) 98.9% Impact toughness <![CDATA[3.83kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 107.22MPa Vickers hardness <![CDATA[681kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.2]]>

[0055] Example 4: A low temperature fired white Yellow River sediment glass-ceramic

[0056] The raw material composition is calculated by weight percentage: Yellow River silt 55.0%, CaCO3 20.9%, dolomite 7.8%, silica sand 6.8%, Na2SiF6 3.1%, K2CO3 2.9%, chromite 2.3%, TiO2 1.2%, plus 1.5% B2O3-CuO oxide of the total weight of the above raw materials.

[0057] The performance requirements of each raw material are the same as those in Example 1.

[0058] Preparation method: Mix the above raw materials evenly and pour them into a lifting muffle furnace, gradually heat them to 1350℃ for sintering, keep them at this temperature for 2h to ensure that all the materials are melted; pour the molten glass into a 600℃ mold, cool it for 30s, and then immediately put the glass plate into a 600℃ muffle furnace, and heat the muffle furnace from 600℃ to 740℃ at a heating rate of 5℃ / min to nucleate the glass plate, and the nucleation time is 3h; heat the muffle furnace to 870℃ at a heating rate of 5℃ / min to crystallize the glass plate, crystallize for 4h, and cool it to room temperature with the furnace to obtain a white microcrystalline glass semi-finished product; cut and polish the semi-finished product to obtain microcrystalline glass. The properties of the obtained microcrystalline glass are shown in Table 4.

[0059] Table 4 Performance indexes of white microcrystalline glass in Example 4

[0060] Performance Indicators result Bulk density <![CDATA[2.67g / cm 3 ]]> Water absorption 0.03% Wear <![CDATA[0.08g / cm 2 <!-- 5 -->]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.0% Alkali resistance (20% NaOH) 98.5% Impact toughness <![CDATA[3.77kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 98.39MPa Vickers hardness <![CDATA[661kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.2]]>

[0061] Example 5: A low temperature fired white Yellow River sediment glass-ceramic

[0062] The raw material composition is calculated by weight percentage: Yellow River silt 53.0%, CaCO3 20.9%, dolomite 7.8%, silica sand 7.8%, Na2SiF6 3.1%, K2CO3 3.9%, chromite 2.3%, TiO2 1.2%, plus 2% B2O3-CuO oxide of the total weight of the above raw materials.

[0063] The performance requirements of each raw material are the same as those in Example 1.

[0064] Preparation method: Mix the above raw materials evenly and pour them into a lifting muffle furnace, sinter at 1350℃, keep warm for 2h, and ensure that all materials are melted; pour the molten glass into a 600℃ mold, cool for 30s, and immediately put the glass plate into a 600℃ muffle furnace, and heat the muffle furnace from 600℃ to 750℃ at a heating rate of 5℃ / min to nucleate the glass plate for 3h; heat the muffle furnace to 900℃ at a heating rate of 5℃ / min to crystallize the glass plate for 2h, and cool to room temperature with the furnace to obtain a white microcrystalline glass semi-finished product; cut and polish the semi-finished product to obtain microcrystalline glass. The properties of the obtained microcrystalline glass are shown in Table 5.

[0065] Table 5 Performance indexes of white microcrystalline glass in Example 5

[0066] Performance Indicators result Bulk density <![CDATA[2.69g / cm 3 ]]> Water absorption 0.04% Wear <![CDATA[0.078g / cm 2 ]]> <![CDATA[Acid resistance (20% H2SO4)]]> 99.1% Alkali resistance (20% NaOH) 98.7% Impact toughness <![CDATA[3.78kJ / m 2 ]]> Resistance to rapid cooling and heating 90% Bending Strength 102.67MPa Vickers hardness <![CDATA[674kgf / mm 2 ]]> radioactivity <![CDATA[I Ra <0.1、I r =0.2]]>

[0067] The SEM images, XRD images, and FTIR images of the glass-ceramics obtained in Examples 2 to 5 are basically the same as those in Example 1 and are not listed one by one.

Claims

1. A low-temperature fired white Yellow River sediment glass-ceramics, characterized in that: The raw material composition by weight percentage is: Yellow River silt 50% to 65%, CaCO3 15% to 25%, dolomite 5% to 10%, silica sand 3% to 10%, Na2SiF6 1% to 5%, K2CO3 1% to 5%, chromite 1% to 5%, TiO2 1% to 5%; in addition, 1% to 4% of the total weight of the raw materials is added in B2O3-CuO oxide.

2. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The pH value of the Yellow River sediment is 7.5-9, and the median particle size D 50 The particle size of the Yellow River silt is 450nm. After being washed and scrubbed, the silt is subjected to magnetic separation to remove the iron-containing substances. The main components of the treated silt are: SiO2 74%-85%, Al2O3 6%-13%, CaO 1%-8%, Fe2O3 0.01%-0.8%, MgO 0.01%-1%, K2O 2%-5%, Na2O 1%-5%, and TiO2 0.01%-1%.

3. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The median particle size D of the dolomite 50 It is 320nm, and its main components are: CaO 63%~70%, MgO 27%~35%, SiO21%~5%, Al2O30.01%~2%, Fe2O30.01%~1%, CuO 0.01%~1%, Cr2O30.01%~1%.

4. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The median particle size D of the silica sand 50 It is 470nm, and its main components are: SiO2 97%~99%, Al2O3 0.01%~3%, K2O 0.01%~1%, CaO 0.01%~1%, Fe2O3 0.01%~1%, Cr2O3 0.01%~1%, TiO2 0.01%~1%, and CuO 0.01%~1%.

5. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The median particle size D of the chromite 50 It is 420nm, and its main components are: Cr2O3 42%~51%, Fe2O3 25%~33%, Al2O3 8%~16%, MgO 5%~10%, SiO2 1%~5%, and TiO2 0.01%~1%.

6. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The CaCO3 purity is greater than 95%, and the median particle size D 50 450nm; Na2SiF6 purity is greater than 95%, D 50 350nm; K2CO3 purity is greater than 95%, D 50 410nm; TiO2 purity is greater than 95%, D 50 It is 370nm.

7. The low temperature fired white Yellow River sediment glass-ceramics as claimed in claim 1, characterized in that: The molar ratio of B2O3 to CuO in the B2O3-CuO oxide is 1:1, wherein the purity of B2O3 is greater than 99%, and D 50 390nm; CuO purity is greater than 99%, D 50 It is 440nm.

8. A low-temperature firing method for the white Yellow River sediment glass-ceramics according to claim 1, characterized in that: The method comprises the following steps: (1) Melting: Put the Yellow River silt into an oven for drying, then mix it with other raw materials in a uniform ratio, pour it into a lifting muffle furnace, slowly heat it to 1330℃~1350℃ for sintering, and keep it at this temperature for 2h~3h to ensure that all the materials are melted to obtain glass liquid; (2) Molding: Pour the molten glass into a mold at 400°C to 600°C and cool for 20s to 30s to obtain a glass plate; (3) Nucleation: Place the glass plate in a muffle furnace, and heat the muffle furnace from 600°C to 720°C to 760°C at a heating rate of 2°C / min to 5°C / min to nucleate the glass plate. The nucleation time is 2h to 4h. (4) Crystallization: The glass plate is crystallized by heating the muffle furnace to 870°C to 920°C at a heating rate of 2°C / min to 5°C / min for 3h to 5h, and then cooled to room temperature in the furnace to obtain a semi-finished glass-ceramic product; (5) Post-processing: The semi-finished glass-ceramic products are cut and polished to obtain the finished products.

Citation Information

Patent Citations

  • A kind of cyanidation tailing foam glass-ceramics and its preparation method

    CN105819695B